The response of selected soil health variables to rainfed and irrigated maize-legume intercropping systems - Nong, Sello Simon (My University, 2022)
Soil health support crop production and answer to its sustainability and renewability. This study involved the use of under explored legumes in South Africa, Limpopo under maizelegume intercropping systems as a strategy to mitigate soil quality deterioration. The study was conducted at University of Limpopo (Syferkuil) and University of Venda (UNIVEN) Experimental farms during 2020/2021. A split plot experiment, with the main factor comprised of water regimes (irrigation and rainfed) and second main factor included cropping systems (Intercropping and monocropping). Five treatments comprised of 3 monocrops (Maize, Chickpea, and Mungbean) and 2 intercrops (maize-chickpea and maize-mungbean) replicated three times. Data collected from the soil before planting and after maturity were pH, Electrical conductivity (EC), particle size, bulk density, aggregate stability, organic matter (OM), organic carbon (OC), phosphorus (P), ammonium (NH4-N), nitrate (NO3—N), soil active carbon (SAC), and potentially mineralizable nitrogen (PMN). Plant parameters collected during vegetative and flowering stage included plant height, chlorophyll content, plant vigour, and leaf area index. All data was subjected to descriptive statistics and analysis of variance using GenStat software. Significant effect (p<0.05) was observed between treatments on soil pH (KCl), OM, organic carbon (OC), and ammonium (NH4) at Syferkuil Farm. Also, interaction between water regimes and cropping systems affected NH4 and pH (KCl). Cropping systems had significant effect (p<0.01) on pH (H2O), OM, OC, P, NH4, and NO3 at UNIVEN. Interaction between water regimes and cropping systems affected (p<0.01) pH (H2O), P but no significant effect was observed on OC, NH4, and NO3. Cropping systems and interaction at both locations did not affect particle size, bulk density, aggregate stability, EC, SAC, and PMN. Pure stands of maize and legumes had greater plant height, plant vigour, and chlorophyll content whereas intercrops had greater LAI. The results at both locations revealed that legume intercropping systems improved soil health variables without posing negative feedbacks and hence can be used to boost soil functioning. Keywords: Soil health, maize-legume intercropping, soil quality
Thesis (M.Sc. Agriculture (Soil Science)) -- University of Limpopo, 2022
Keywords: Soil health; Maize-legume intercropping; Soil quality; Intercropping; Soils; Soil fertility; Rhizobacteria; Crops; Crop yields; Legumes; Dry farming